Lead In drinking water: Adsorption method and role of zeolitic imidazolate frameworks for its remediation: A review. (25th September 2022) - Ahmad, Khalil; Shah, Habib-ur-Rehman; Khan, Muhammad Shahzeb; Iqbal, Amjad; Potrich, Erich; Amaral, Larissa Souza; Rasheed, Sidra; Nawaz, Haq; Ayub, Asif; Naseem, Khalida; Muhammad, Ali; Yaqoob, Muhammad Rashid; et al.
Abstract: Due to various characteristics properties lead(II) metal is utilized in many applications like lead ion batteries, water pipes, ammunition and paints. For this reason, concentration of lead(II) ions in water is increasing days by days which is alarming for water pollution. Water pollution is a major problem worldwide which affects biosphere badly, and causes continuous reduction of accessible sources of fresh water and ground water, available for drinking purpose. From these pollutants lead is highly toxic metal which badly affects humans as well as aquatic organisms. Due to its toxic and non-degradable nature, it is listed in top ten hazardous metals. Various adsorbents are applied for removal of lead from water. Recently, Zeolitic Imidazolate Frameworks a subclass of Metal Organic Frameworks introduced by Yaghi group having outstanding stability and porosity are applied for removal of lead from water using adsorption method as reported in many studies. In this review recent progresses for removal of lead from water by adsorption method using ZIF-8 and ZIF-67 MOFs are discussed in detail. Adsorption mechanism includes electrostatic/coordination interactions, π-π-stacking and ion exchange method for lead removal from aqueous medium are discussed in detail. Pseudo 2nd order-equation and Langmuir model are well fitted for elucidation of adsorption mechanism for lead removal. Graphical abstract: Image Highlights: We discuss the sources, chemistry and toxicity of lead species in water systems. Adsorption method for the removal of lead are presented with improved and enhanced efficiency. The need and potential of ZIFs as adsorbent have been indicated for the said purpose. ZIFs are sustainable in terms of economics, reusability and ecofriendly environment. Thereby, some key areas have also been highlighted for further research in this domain.